Nitazoxanide, an Antiprotozoal Drug, Reduces Bone Loss in Ovariectomized Mice by Inhibition of RANKL-Induced Osteoclastogenesis - Li, Chang-hong; Lü, Zi-rui; Zhao, Zhen-da; Wang, Xin-yu; Leng, Hui-jie; Niu, Yan; Wang, Mo-pei (Frontiers in Pharmacology, 2021)
Nitazoxanide (NTZ) is an FDA-approved anti-parasitic drug with broad-spectrum anti-infective, anti-inflammatory, and antineoplastic potential. However, its regulatory effects on osteoclastogenesis and the underlying mechanisms remain unclear. The present study found that NTZ potently inhibited osteoclast formation at the early stage of receptor activator of NF-κB ligand-induced osteoclastogenesis in a concentration-dependent manner at a non-growth inhibitory concentration. NTZ suppressed actin ring formation and decreased osteoclast marker gene expression, including TRAP, MMP9, and cathepsin K. NTZ significantly impaired the bone resorption activity of osteoclasts. In vivo, ovariectomized mice were treated with 50, 100 and 200mg/kg/d NTZ for 3 months. NTZ (100mg/kg/d) administration markedly reduced ovariectomy-induced bone loss by suppressing osteoclast activity. Mechanistically, osteoclastogenesis blockade elicited by NTZ resulted from inhibition of STAT3 phosphorylation, and reduction of the Ca2+ fluorescence intensity and NFATc1 expression. NTZ weakened the binding between STAT3 and the NFATc1 promoter region. Furthermore, enforced NFATc1 expression partly rescued the impaired osteoclast differentiation in NTZ-treated RAW264.7 cells. In summary, NTZ could inhibit osteoclastogenesis and bone loss through modulation of the receptor activator of NF-κB ligand-induced STAT3-NFATc1 signaling pathway, which might be a potential alternative treatment regimen against bone destruction-related diseases including osteoporosis.